2019
DOI: 10.3390/cancers11081085
|View full text |Cite
|
Sign up to set email alerts
|

Current State of Liver-Directed Therapies and Combinatory Approaches with Systemic Therapy in Hepatocellular Carcinoma (HCC)

Abstract: The increasing set of liver-directed therapies (LDT) have become an integral part of hepatocellular carcinoma (HCC) treatment. These range from percutaneous ablative techniques to arterial embolization, and varied radiotherapy strategies. They are now used for local disease control, symptom palliation, and bold curative strategies. The big challenge in the face of these innovative and sometimes overlapping technologies is to identify the best opportunity of use. In real practice, many patients may take benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 106 publications
(129 reference statements)
2
48
0
Order By: Relevance
“…Studies have demonstrated that TACE activates a hypoxic response, promoting the release of vascular endothelial growth factor (VEGF) and other proangiogenic cytokines (Sergio et al, 2008 ; Viveiros et al, 2019 ). Additionally, cell necrosis induced by TACE is predicted to be associated with antigen release and the exposure of damage-associated molecular patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that TACE activates a hypoxic response, promoting the release of vascular endothelial growth factor (VEGF) and other proangiogenic cytokines (Sergio et al, 2008 ; Viveiros et al, 2019 ). Additionally, cell necrosis induced by TACE is predicted to be associated with antigen release and the exposure of damage-associated molecular patterns.…”
Section: Discussionmentioning
confidence: 99%
“…7 Local modalities for treating HCC include ablative therapies, such as radiofrequency ablation, and locoregional therapy such as transarterial chemoembolisation (TACE), transarterial radio embolisation (TARE) and stereotactic ablative radiotherapy (SABR). 8 For patients with advanced multifocal disease, the kinase inhibitor sorafenib has been shown to be effective in Childs Pugh Class A cirrhosis with unresectable hepatocellular carcinoma.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…Liver transplant has proven successful in treating cases of early stage HCC, but only an even smaller proportion of patients are eligible due to the late diagnosis of the disease and limited organ availability [5,6]. Other local strategies, such as transarterial chemo-embolization, radioembolization, and radiofrequency ablation, are largely palliative [7].…”
Section: Introductionmentioning
confidence: 99%